DIGITAL CONTROL OF SWITCHING POWER CONVERTERS - HASSAN, RUBIAH (Universiti Teknologi Petronas, 2006)
This report describes the design of a digital controller that capable to control the switching action of Buck converter. It focuses on how to generate the DPWM signal in order to vary the ON/OFF condition of the low powerBuck converter switch. The main objective of this project is to have a controller that capable to produce a stable and high resolution of output voltage with high switching frequency response. Two (2) types of computer simulation have been carried out in this project which are the PSpice and MATLAB simulation. The PSpice simulation has been used to verify that the calculated parameters confirm the Buck converter operating in continuous conduction mode. The simulation results obtained in the PSpice simulation have been verified that the calculated parameters such resistor, inductor and capacitor value can be used for Buck converter circuit operating in continuous conduction mode. All the results obtained, except for the output current ripple are within ±10 % acceptable limit of percentage differences with its design requirements. The MATLAB simulation has been used to design the Buck converter system together with its digital controller part. The simulation results in MATLAB do not achieve the desired objectives because of the problem in setting the PID compensator coefficient which leads to a few simulation errors.